Potential analysis of small and medium industries (SMIs) in Lima Puluh Kota Regency, West Sumatra - Elfi Khairina; Adrimas Adrimas; Sjafrizal Sjafrizal (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Small and Medium Industries (SMIs) play an important role in the industrial sector of the Lima Puluh Kota Regency, even though the growth rate has fluctuated in the last six years. The purpose of this study is to identify the potential of Small and Medium Industries (SMIs) Lima Puluh Kota Regency that have comparative and competitive advantages. The analytical methods are location quotient (LQ) and shift-share analysis. Using a variable value of industrial production based on Indonesian Standard Business Classification in five digits of industrial commodity was found, the basic organic chemical industry for raw materials for dyes and pigments, embroidery industry, wood container industry, garment industry of leather, industrial stone goods for home use stairs and displays, the gypsum industry, the components and equipment industry of two- and three-wheeled motorcycles, the soft drink industry and the coconut oil industry are industries that have a comparative as well as a competitive advantage. These industries are suggested to be lead industries in the development of Small and Medium Industries (SMIs) in Lima Puluh Kota Regency.